Tính chất của copolyme trên cơ sở polylactic axit ghép chitosan - Hoàng, Thái; Tuấn, Vũ Mạnh; Thu Trang, Nguyễn Thị; Chinh, Nguyễn Thúy (Vietnam Journal of Chemistry, 2015)
This study expresses the preparation and characterization of polylactic acid graft chitosan copolymer (PLA-g-CS) based on the copolymerization using the initiator and crosslink agent by free radical mechanism. The Fourier Infrared Spectra (FTIR) of PLA-g-CS copolymer shows that PLA and CS were successfully grafted. The thermal stability of PLA-g-CS copolymer is enhanced due to the formation of hyper-crosslinked structure during the copolymerization process. The output of copolymerization reaction was calculated according to the Thermo Gravimetric Analysis (TGA) method. The degradability of PLA-g-CS copolymer was also investigated by the weight loss of copolymers and the FESEM images of those samples that were immersed in solutions with different pH values.